Analisis Nilai Moral Novel Kembara Karya Pradana Boy ZTF - Pendi Susilo; Agung Nugroho; Inda Puspita Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study is to describe the moral values ​​contained in the novel Kembara Karya Pradana Boy ZTF. This study uses qualitative methods with qualitative descriptive research on documents in the form of the novel Kembara Karya Pradana Boy ZTF as the data source. Data collection techniques in this study with documentation techniques. From the results of data analysis, it is known that the novel Kembara Karya Pradana Boy ZTF has moral values ​​according to the regulations. The conclusions that can be drawn from this research are, a) moral values ​​in human relations with oneself there are 30 quotes; b) human moral values ​​with other humans there are 26 quotes; c) human moral values ​​with God there are 31 quotes. Keywords: Kembara, Moral Values, Pradana Boy ZTF